2017
DOI: 10.1016/j.jhep.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota contributes to a mouse model of spontaneous bile duct inflammation

Abstract: Background & Aims A strong association between human inflammatory biliary diseases and gut inflammation has led to the hypothesis that gut microbes and lymphocytes activated in the intestine play a role in biliary inflammation. The NOD.c3c4 mouse model develops spontaneous biliary inflammation in extra- and intra-hepatic bile ducts. We aimed to clarify the role of the gut microbiota in the biliary disease of NOD.c3c4 mice. Methods We sampled cecal content and mucosa from conventionally raised (CONV-R) NOD.c3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 36 publications
(41 reference statements)
1
59
0
Order By: Relevance
“…Several mechanisms may explain the increase of the bile acids pool, including upregulation of cholesterol 7α‐hydroxylase (Cyp7A1) induced by both chronic and acute alcohol consumption and/or a decrease in bile acids excretion in the bile and subsequent release in the plasma in the context of AH. Moreover, it has also been suggested that the intestinal microbiota can contribute to biliary inflammation, which could impair bile acids circulation. These hypotheses are supported by the increased levels of primary and conjugated plasma bile acids in the Cir_sAH patients and decrease in the proportion of secondary plasma bile acids and total faecal bile acids.…”
Section: Discussionmentioning
confidence: 71%
“…Several mechanisms may explain the increase of the bile acids pool, including upregulation of cholesterol 7α‐hydroxylase (Cyp7A1) induced by both chronic and acute alcohol consumption and/or a decrease in bile acids excretion in the bile and subsequent release in the plasma in the context of AH. Moreover, it has also been suggested that the intestinal microbiota can contribute to biliary inflammation, which could impair bile acids circulation. These hypotheses are supported by the increased levels of primary and conjugated plasma bile acids in the Cir_sAH patients and decrease in the proportion of secondary plasma bile acids and total faecal bile acids.…”
Section: Discussionmentioning
confidence: 71%
“…While in models of acute hepatic injury such as acetaminophen- and alcohol-induced hepatotoxicity GF mice were protected from hepatic disease 25, 26 . In a spontaneous biliary inflammation model, GF NOD.c3c4 mice develop a milder biliary affection compared with conventionally raised NOD.c3c4 mice 9 . It might be that in those models immune-mediated mechanisms were dominant, and the microbiota might be participated in immune cell activation.…”
Section: Discussionmentioning
confidence: 95%
“…The gut microbiota can influence or modulate chronic liver disease 7 . In the absence of the intestinal microbiota, germ-free mdr2 -/- mice had exacerbated primary sclerosing cholangitis 8 , while germ-free NOD.c3c4 mice had attenuated spontaneous biliary inflammation 9 . Whether the gut microbiota participates in the hepatobiliary pathogenesis during C. sinensis infection is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The sections were blindly scored on the following parameters: portal inflammation (0–3), dilatations of intrahepatic bile ducts (0–3), fibrosis (0–3), and bile infarcts (0–2), where a score of 0 indicates no pathology, as previously described (Schrumpf et al. ). Portal inflammation and dilatation of intrahepatic bile ducts are the two most pronounced features in this mouse model (Koarada et al.…”
Section: Methodsmentioning
confidence: 99%